Export competitiveness of agri-food sector during the EU integration process: Evidence from the Western Balkans - Bojan Matkovski; Stanislav Zekić; Danilo okić; Žana Jurjević; Ivan urić (Foods, 2022)
Trade agreements with the European Union (EU) and Central European Free Trade Agreement (CEFTA) significantly influenced the liberalisation of agri-food products in Western Balkan (WB) countries. In all Western Balkan countries, there has been an intensification of the trade of agri-food products and a partial change in the regional and commodity structures of trade. This paper aims to identify comparative advantages of agri-food sectors and consider its tendencies during the EU integration process. Additionally, this paper will discuss some opportunities for improvement of the export positions of agri-food products. In that context and based on the literature review, the indexes of revealed comparative advantages and its modified version will be used as a main method for analysis in this research. Results showed that all Western Balkan countries, except Albania, have comparative advantages in exporting agri-food products. It is evident that Serbia has the highest level of comparative advantages in this sector. Moreover, this paper suggests that all countries should aim to provide the best possible positions for their agri-food products during pre-accession negotiations for EU membership and take the necessary steps towards increasing the level of competitiveness in the common EU market.
Keywords: 330; agri-food; competitiveness; European Union; Western Balkans